The Decency of Strength and the Strength of Decency: A Philosophical Approach to the Sport of Wrestling. Issue 1 (2nd January 2016) - Kameas, Nikolaos; Albanidis, Evangelos; Barbas, Ioannis
ABSTRACT: The standard of the ancient Greek ideal of noble competition, timelessly constitutes the ultimate proposal for decent manifestation of human strength on all levels: physical/somatic, intellectual, emotional, mental, and spiritual. The logic of sportsmanship in ancient Greek culture, especially in athletics and education, contains in its core the sport of wrestling. Thus, in this study, the qualitative characteristics of wrestling were analyzed to demonstrate—philosophically—the value of this sport as a chance/possibility for development and culturing of human existence. Reference points of this study were as follows: (a) the ancient Greek literature (Homer, Pindar, Isocrates, Xenophon Lucian, ), (b) ancient Greek philosophers (Heraclitus, Empedocles, Plato, Aristotle), (c) modern philosophers (Friedrich Nietzsche), and (d) contemporary studiers. The reasoning course of the study was initiated by the primary struggle of natural elements and the presence of primordial war instinct in Man, (b) continued with the beneficial influence of the ancient Greek athletic standard of fair play in the totality of human nature, and (c) the central role of wrestling in the edifice of the agonistic ancient Greek civilization emerged while stressing the moral, intellectual, and spiritual dimension of this sport and its distinct pedagogical value timelessly.